Guide to the presidency - Nelson, Michael (Congressional quarterly, 1996)
This two-volume work traces the history and development of the American presidency from George Washington to Bill Clinton. It features examinations of presidential selection and removal; presidential powers; the president and the public; the White House and executive branch; and more.